Milieudefensie v Shel: a Pyrrhic victory for climate change litigation - Zambrana Tévar, Nicolás (CUADERNOS DE DERECHO TRANSNACIONAL, 2025)
The Court of Appeal of The Hague confirms that companies have responsibilities under international human rights law concerning the need to achieve the emission reduction targets established by the 2015 Paris Agreement and applying various international soft law instruments. However, these norms do not establish a specific level of emission reductions such companies must comply with.
Keywords: climate change; litigation; emissions; human rights; torts